(untitled) (Journal of the College of Education for Women, 2019)
Besides the role of state institutions that come in the forefront of their priorities and obligations to provide security and development of the economy and reduce the unemployment rate and the reduction of inflation and improving education, health and others, the Community Partnership At frames what has become known as the institutions of society civil-with the state does not eliminate the role, but rather complements its role ; it is the role of civil society partner and an extension of the role of the state in the face of challenges and crises, but it may be sometimes a race role in addressing social, political and economic issues of the role played by the state, not complementary.The highlighting the specificity of the relationship between the youth site within the institutions of civil society and development highlights the importance of the role of these institutions in the rehabilitation of young leaders in various fields, and to raise the sense of national belonging, and the establishment of democracy and respect for human rights values, and then enable the integration into the overall development paths.